2007
DOI: 10.1111/j.1541-0420.2007.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Type I and Type II Error Under Random‐Effects Misspecification in Generalized Linear Mixed Models

Abstract: Generalized linear mixed models (GLMMs) have become a frequently used tool for the analysis of non-Gaussian longitudinal data. Estimation is based on maximum likelihood theory, which assumes that the underlying probability model is correctly specified. Recent research is showing that the results obtained from these models are not always robust against departures from the assumptions on which these models are based. In the present work we have used simulations with a logistic random-intercept model to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
3
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 21 publications
6
110
3
7
Order By: Relevance
“…Note that this theory can also be regarded as the underpinning of such commonly used methods as generalized estimating equations. This methodology has been applied by Litiére et al [37,38] in the context of miss-specification arising from the random-effects distribution in generalized linear mixed models. Moreover, we did not address the effect of ignoring the correlated frailty structure by using a shared frailty distribution on the estimation of covariate effects.…”
Section: Discussionmentioning
confidence: 99%
“…Note that this theory can also be regarded as the underpinning of such commonly used methods as generalized estimating equations. This methodology has been applied by Litiére et al [37,38] in the context of miss-specification arising from the random-effects distribution in generalized linear mixed models. Moreover, we did not address the effect of ignoring the correlated frailty structure by using a shared frailty distribution on the estimation of covariate effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of mixed models for binary responses, Agresti, Caffo, and OhmanStrickland (2004) have found that inferences tend to be unbiased under general departures from normality and only found a drop in efficiency when the random effects' true distribution is discrete with large variance. As a matter of fact, for this type of model Litière, Alonso, and Molenberghs (2007) formally showed (see their theorem 1 and corollary 1) that a significant finding (i.e., β significantly different from zero) is a reliable result even under a misspecified distribution of the random effects. We make this normality assumption because (i) it allows us to use two-step estimation methods instead of direct maximum likelihood and (ii) it yields closed-form E-and M-steps in the EM-algorithm that we propose for the second step of the two-step estimation procedure.…”
Section: Two-step Estimationmentioning
confidence: 90%
“…Very often such random effects are assumed to be normally distributed. The normality assumption for the random effects has been both criticised and supported by several authors [25,26,27].…”
Section: Discussionmentioning
confidence: 99%